Exploring the relationship between occupational stress, physical activity and sedentary behavior using the Job-Demand-Control Model - Clinchamps, Maëlys; Bibily, Céline; Bouillon-Minois, Jean-Baptiste; Ugbolue, Ukadike C.; Trousselard, Marion; Pereira, Bruno; Dutheil, Frédéric (Frontiers in Public Health, 2024)
ObjectivesTo study the relationship between the occupational stress model, specifically the Job Demand-Control Model of Karasek, physical activity level and sedentary behavior.MethodThis is a cross-sectional, observational, descriptive study. A self-administered questionnaire was distributed to 100 volunteers working at Clermont Auvergne University. The questionnaire included the Karasek questionnaire and the International Physical Activity Questionnaire.ResultsThe results reveal that occupational characteristics play a significant role, with individuals exhibiting high job control showing reduced sitting time and increased physical activity compared to those with low job control. Job strain was associated with increased sitting time and decreased physical activity. Further analysis revealed that being in a state of job strain significantly predicted sitting for more than 7 h per day. Similarly, job strain and isostrain were explanatory factors for having a low to moderate physical activity level. Logistic regression quantified the risks, indicating that sitting for more than 7 h per day increased the risk of job strain by 4.80 times, while high physical activity levels and being male reduced the risk by 79 and 84%, respectively. Job strain also increased the risk of prolonged sitting by 5.06 times and low to moderate physical activity levels by 5.15 times. Additionally, mediation analysis revealed that a substantial portion of the association between sitting time and job strain was mediated by physical activity, and vice versa, emphasizing the interconnected nature of sedentary behavior and physical activity in influencing occupational stress.ConclusionThe study highlights the impact of sedentary behavior on occupational stress, assessed using Karasek’s Job-Demand-Control Model. Despite being less studied, sedentary behavior appears to be a relevant contributor to occupational stress. Furthermore, the results emphasize the significant role of physical activity levels, suggesting that it plays a substantial part in the relationship between sedentary behavior and occupational stress.